1985
DOI: 10.1148/radiology.156.2.3892580
|View full text |Cite
|
Sign up to set email alerts
|

Venous renal tumor extension: a prospective US evaluation.

Abstract: To evaluate the ability of ultrasonography (US) to determine venous tumor extension, we studied 120 consecutive patients with renal neoplasms. The incidence of renal vein involvement in this group was 18%; caval tumor extension occurred in 11% of the patients. Real-time US clearly visualized the entire retrohepatic inferior vena cava (IVC) in 96% of the examinations, and the ipsilateral renal vein was well seen on 88% of the scans. Of the caval sonograms that could be evaluated (115/120), intravascular tumor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
5

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 0 publications
0
7
0
5
Order By: Relevance
“…Although there have been previous studies of the staging of renal carcinoma by ultrasonography, the majority have examined a single staging criterion such as venous tumour extension (Schwerk et al, 1985) or the "T" stage (Frohmuller etal., 1987). Cronan et al (1982) looked at overall tumour staging by ultrasonography and found it to have an accuracy of 70% (16 of 23 patients).…”
Section: Resultsmentioning
confidence: 99%
“…Although there have been previous studies of the staging of renal carcinoma by ultrasonography, the majority have examined a single staging criterion such as venous tumour extension (Schwerk et al, 1985) or the "T" stage (Frohmuller etal., 1987). Cronan et al (1982) looked at overall tumour staging by ultrasonography and found it to have an accuracy of 70% (16 of 23 patients).…”
Section: Resultsmentioning
confidence: 99%
“…If the tumor thrombus involves the intrahepatic portion of the vena cava, ultrasound sensitivity of 100% has been reported in detecting the tumor thrombus. Usually the overall sensitivity of detecting a thrombus is reported from 89 to 100% 13,14 (Fig. 3A).…”
Section: Discussionmentioning
confidence: 99%
“…When, as in the case on record, an intraluminal mass is incidentally found in the inferior vena cava, the differential diagnosis includes intravenous extension of a renal carcinoma, a fairly frequent phenomenon. In a recent study comprising 120 unselected patients with renal neoplasms, 13 patients (10.8%) had tumor growth into the inferior vena cava (13). Other possibilities when a tumorlike lesion is found in the inferior vena cava are extension into the vessel from thrombosis of pelvic veins and rare occasions of extended growth from intravenous uterine leiomyomatosis (1 8), renal angiomyolipoma (7), xanthogranulomatous pyelonephritis (9), adrenal carcinoma ( 1 1) and pheochromocytoma (12).…”
Section: Discussionmentioning
confidence: 99%